Safety and efficacy of endovenous laser ablation (EVLA) using 1940 nm and radial emitting fiber: 3‐year results of a prospective, non‐randomized study and comparison with 1470 nm. Issue 4 (5th December 2021) - Setia, Abhay; Schmedt, Claus‐Georg; Beisswenger, Anna; Dikic, Slobodan; Demhasaj, Sahit; Setia, Ocean; Schmitz‐Rixen, Thomas; Sroka, Ronald
Abstract: Objectives: To evaluate the safety, efficacy and ≥36 months outcomes of endovenous laser ablation (EVLA) by means of 1940 nm laser with radial fiber for the treatment of truncal vein insufficiency and compare the results to a historical cohort, obtained via reviewing the literature. Methods: This prospective, non‐randomized, single‐center clinical study included 139 consecutive patients with 177 incompetent great saphenous (GSV, n = 135) and short saphenous veins (SSV, n = 42). The maximum laser power ( P max. 10 W) and pullback velocity were adjusted individually ( V max = 1 mm/s). The laser fiber was placed at the junction to the deep vein under duplex monitoring. Simultaneous phlebectomies were performed on all the patients. Regular follow up with clinical and duplex ultrasound examination (DUS) were carried out postoperatively at 1 month (1 M), 6 months (6 M), 12 months (12 M), 24 months (24 M), 36 months, and after that (≥36 M). The results were compared with three cohorts (total 616 EVLA procedures with 1470 nm laser and radial fiber) from literature (criteria: >100 procedures, follow‐up of ≥2 years). Results: The follow‐up rate was 100%, 91%, 73%, 48%, and 23% of the truncal veins at 1, 6, 12, 24, and ≥36 M, respectively. In comparison to the literature using 1470, a lower average linear endovenous energy density (LEED) (53 vs. 77–82 J/cm) resulted in 100% (6 M) and 96.5% (24 M) occlusion rates, reduced local ecchymosis (2.2% vs. 3.2%–18.7%) and reduced average postoperative pain levels (1.3 vs. 2.18). Regarding adverse events, induration (1.1% vs. 1.8%), skin burns (0% vs. 0.45%), endovenous heat‐induced thrombus propagation (EHIT) in the deep veins (2.3% vs. 1.8%) and laser‐induced persistent paresthesia (2.2% vs. 0.5%–2.9%) were comparable. Recanalizations observed in this study (GSV 0, SSV 3) were asymptomatic and required no treatment. At ≥36 M reflux in the accessory veins was observed in 5% versus 10.5% of patients. Reintervention was required in none (0% vs. 21%). At >36 M, short average stump lengths of 1 cm (GSV) and 0.3 cm (SSV) were observed. Conclusion: EVLA with 1940 nm laser with radial emitting fiber is as safe and effective as 1470 nm laser for the treatment of truncal vein insufficiency. Lower postoperative pain, low analgesic requirements, short convalescence add to patients' comfort. EVLA with 1940 nm laser‐guided by intraoperative DUS permits reproducible placement of the radial fiber at the saphenofemoral and saphenopopliteal junction, enabling further studies to assess the effect of shorter stump length on patterns and frequency of recurrence without increased risk of EHIT.